2011
DOI: 10.1002/hyp.8295
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the dependencies of rainfall‐runoff responses on human forest disturbances with soil loss based on the runoff mechanisms in granite and sedimentary rock mountains

Abstract: Abstract:Understanding the effects of severe human induced forest disturbances with soil loss on rainfall-runoff responses is important for future forest management. However, few studies have addressed this issue, which is methodologically difficult compared with the hydrological assessments of the effects of logging. In this study, several small catchments in Japan with different soil and geological conditions were compared using the runoff model HYCYMODEL to reveal their runoff characteristics. The results w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 62 publications
0
21
0
Order By: Relevance
“…Tani et al [3] showed a flow duration curve from hourly runoff volume for 1 year obtained by calculations, The annual maximum hour runoff volume (left end of flow duration curve) and annual minimum hour runoff volume (right end of flow duration curve) are shown in Table 1.…”
Section: Results Of Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…Tani et al [3] showed a flow duration curve from hourly runoff volume for 1 year obtained by calculations, The annual maximum hour runoff volume (left end of flow duration curve) and annual minimum hour runoff volume (right end of flow duration curve) are shown in Table 1.…”
Section: Results Of Evaluationmentioning
confidence: 99%
“…F2 catchment belongs to the temple established in the 9th century. The forest soil in F2 catchment is well developed as classified into brown forest soil noted by Tani et al [3]. The forest ages are 0 year for Rachi (bare) catchment, 46 years for Jakujo and 106 years for Kiryu, when runoff volume data were observed to identify the parameters by Tani et al [3].…”
Section: Evaluation Of Forest Maturity and Forest Functionsmentioning
confidence: 98%
See 1 more Smart Citation
“…If the drainage capacity of the downslope flow is so large that the storage change in response to the flow rate is negligible compared to that in the vertical unsaturated flow, the dependence of the RBPI values on slope length may almost disappear, as shown in the right panel of Fig. 6; these values may also differ from those predicted by a distributed runoff model in which the 4464 Makoto Tani: A paradigm shift in stormflow predictions stormflow component is represented by only a downslopeflow component (Ishihara and Takasao, 1964;Troch et al, 2003). The dependence of stormflow responses on unsaturated vertical flow has often been discussed from on-site observations (Montgomery and Dietrich, 2002) and from theoretical considerations (Tani, 1985a;Kosugi, 1999).…”
Section: A Possible Modelling Strategymentioning
confidence: 99%
“…The vegetation of the study area is a planted forest, primarily consisting of Chamaecyparis obtusa (Japanese cypress) and Cryptomeria japonica (Japanese cedar), which were both planted in the 1950s (Tani et al, 2012). Every catchment in this study area is covered with brown forest soil (Tani et al, 2012), which is typical of low relief mountains in Japan.…”
Section: Study Sitementioning
confidence: 99%